SERVET-İ FÜNUN ŞİİRİNDE MODERNİZM VE MODERNİTE - İŞLER, İLKER (Fırat Üniveristesi, 2011)
Bu çalışmanın temel amacı, modern ve türevlerinin en önemli unsurlarından olan modernizm ve modernitenin, Yeni Türk şiirinin en önemli dönemlerinden olan Servet-i Fünun dönemi şiirine nasıl yansıdığını ortaya koymaktır. Modern ve türevlerinin en önemli iki unsuru olan modernizm ve modernite, insanın bütün üretimlerine damgasını güçlü bir şekilde vurmuştur. Bu durumun, insanlığın sonuna kadar devam edeceği malumdur. Bu açıdan modernizm ve modernite daima edebiyatta ve şiirde yansımasını bulacaktır.Bu kavramlar çerçevesinde şekillenen çalışmamızda, sosyoloji ve tarih biliminin verilerinden de faydalanılmıştır. Ayrıca, konunun kültürel, siyasi, dini yönleri de ele alınmıştır.

The main goal of this paper is to illustrate how modernism and modernity which are the most important elements of modern and its other kinds reflect to Servet-i Fünun that is one of the most significant periods of new Turkish poem. Two of the most important elements of modern and its other kinds, modernism and modernity affected powerfully to the all productions of human being. It is obvious that this situation will continue until the end of the human kind. That?s why modernism and modernity is always going to be found in the literature and poem.In the paper which has been written in the frame of these concepts, it has been made use of data from sociology and science of history. Besides; cultural, political, religious dimensions of subject has been argued.
Modernism and modernity in the poems of Servet-i Fünun
Keywords: Türk Dili ve Edebiyatı